Polyamines control of cation transport across plant membranes: implications for ion homeostasis and abiotic stress signaling - Pottosin, Igor; Shabala, Sergey (Frontiers in Plant Science, 2014)
Polyamines are unique polycationic metabolites, controlling a variety of vital functions in plants, including growth and stress responses. Over the last two decades a bulk of data was accumulated providing explicit evidence that polyamines play an essential role in regulating plant membrane transport. The most straightforward example is a blockage of the two major vacuolar cation channels, namely slow (SV) and fast (FV) activating ones, by the micromolar concentrations of polyamines. This effect is direct and fully reversible, with a potency descending in a sequence Spm4+>Spd3+ >Put2+. On the contrary, effects of polyamines on the plasma membrane cation and K+-selective channels are hardly dependent on polyamine species, display a relatively low affinity, and are likely to be indirect. Polyamines also affect vacuolar and plasma membrane H+ pumps and Ca2+ pump of the plasma membrane. On the other hand, catabolisation of polyamines generates H2O2 and other reactive oxygen species, including hydroxyl radicals. Export of polyamines to the apoplast and their oxidation there by available amine oxidases results in the induction of a novel ion conductance and confers Ca2+ influx across the plasma membrane. This mechanism, initially established for plant responses to pathogen attack (including a hypersensitive response), has been recently shown to mediate plant responses to a variety of abiotic stresses. In this review we summarize the effects of polyamines and their catabolites on cation transport in plants and discuss the implications of these effects for ion homeostasis, signaling, and plant adaptive responses to environment.